2019
DOI: 10.1016/j.jpainsymman.2019.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Related Pain: A Longitudinal Study of Time to Stable Pain Control and Its Clinicodemographic Predictors

Abstract: Context. Multidimensional assessment is pivotal in managing cancer-related pain. Objectives. The objectives of this study were to determine time to stable pain control (SPC) and identify its baseline clinicodemographic predictors in patients with cancer pain. Methods. This is a prospective longitudinal study of patients attending a cancer pain clinic. Scheduled clinic attendances and weekly investigator-led phone calls enabled monitoring of patients' daily pain diary, opioid use, and other analgesic interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
2
4
0
1
Order By: Relevance
“…Using the group of patients with only bone pain as comparator, patients with only soft tissue pain and only visceral lesions have lower pain intensity levels, whereas, those with the association of soft and nervous tissue pains have higher pain intensities during follow-up ( Figure 2 ). Similar findings were reported in another study, which also identified soft tissue pain as associated to shorter time for achieving pain control 31 but the authors do not provide information on how the classification was performed and whether patients had one or more types of pains.…”
Section: Discussionsupporting
confidence: 56%
“…Using the group of patients with only bone pain as comparator, patients with only soft tissue pain and only visceral lesions have lower pain intensity levels, whereas, those with the association of soft and nervous tissue pains have higher pain intensities during follow-up ( Figure 2 ). Similar findings were reported in another study, which also identified soft tissue pain as associated to shorter time for achieving pain control 31 but the authors do not provide information on how the classification was performed and whether patients had one or more types of pains.…”
Section: Discussionsupporting
confidence: 56%
“…Baseline pain intensity and vital signs were identified as high-risk predictors for cancer-related pain [12, 41]. In a previous study, we established a correlation between vital signs, baseline pain scores, and the intensity of pain during RT for patients with OC/OPC [12].…”
Section: Discussionmentioning
confidence: 99%
“…Evidência quanto à efetividade da filosofia dos CP no manejo adequado da dor também é ratificada em estudo prospectivo longitudinal. Nesse, os cuidados baseados no conforto como também o tratamento farmacológico concreto reduziu consideravelmente a dor (18) . O cansaço, também denominado fadiga, por ser um sintoma de difícil definição devido ao seu conceito multicausal e multidimensional (19) , apresentou piora do score.…”
Section: Discussionunclassified